Pengembangan Media Pembelajaran Berbasis Website “Geo Me Try” untuk Meningkatkan Pemahaman Konsep Luas Bangun Datar Peserta Didik Kelas 4 Sekolah Dasar - Veronica Prima Damayanti Bandaso; Nyoto Harjono (Peneliti.net, 2023)
The high interest of students in mathematics has not yet shown the achievement of maximum learning outcomes. The difficulty of students in understanding the basic concept of the area of a flat shape and the lack of supporting learning media in the teaching and learning process are factors that are not optimal in student learning outcomes. This is the main reason to create a breakthrough on this phenomenon. Through the development of learning media based on the website